Quality control of the Greek sausages during the last ten years 1967- 1976 - ΠΑΠΑΔΟΠΟΥΛΟΣ ΧΡΥΣΑΝΘΟΣ ΤΡΥΦ. (Journal of the Hellenic Veterinary Medical Society, 2019)
During the last decade 1967-1976, were examined in the Histopathology Department 8263 samples From different types of sausages produced in Greece. I he total of the samples was examined histologically in paraffin sections. The relative procedures of the followed techniques are described in detail. I rom the 8263 samples, the 6740 (81.57%) were normal, it means entirely free from every foreign substance. The 1523 samples (18.43%) presented different foreign substaces, in large, medium, or small quantities. I he foreign tissues and organs found, were mainly salivary glands, mouth mucosal tissue, epidermal layers of pig’s skin with or without hairs, mammary glandular tissue, cartilage tissue, lung’ s tissue, parts of the uterus wall and parts of the gastrointestinal truct. I he large part of the foreign materials detected in cooking sausages (19.50%) and the small part in the meat mass of the dry sausages (16.54%). I he importance of the histological control in the sausages, is mentioned at the end of the study. I he histological examination can determine, with a relative accuracy, the percentage of collagen and others fibrous elements of the connective tissue, and mainly the source of their origin. I he collagen fibers are very indigestible and their nourishing value low, their presence in sausages reduces the nutritional value and the quality of them.